Effect of delaying same-admission cholecystectomy on outcomes in patients with diabetes. Issue 2 (16th December 2013) - Gelbard, R; Karamanos, E; Teixeira, P G; Beale, E; Talving, P; Inaba, K; Demetriades, D
Abstract: Background: Recent studies have suggested that same-admission delayed cholecystectomy is a safe option. Patients with diabetes have been shown to have less favourable outcomes after cholecystectomy, but the impact of timing of operation for acute cholecystitis during the same admission is unknown. Methods: This was a retrospective analysis of patients undergoing laparoscopic cholecystectomy for acute cholecystitis between 2004 and 2010, from the American College of Surgeons National Surgical Quality Improvement Program database. Patients with no significant co-morbidities (American Society of Anesthesiologists grade I or II) were included. Propensity score matching (PSM) was used to match patients with diabetes with those who did not have diabetes, in a ratio of 1 : 3, to ensure homogeneity of the two groups. Logistic regression models were applied to adjust for differences between early (within 24 h) and delayed (24 h or more) surgical treatment. The primary outcome was development of local and systemic infectious complications. Secondary outcomes were duration of operation and length of hospital stay. Results: From a total of 2892 patients, 144 patients with diabetes were matched with 432 without diabetes by PSM. Delaying cholecystectomy for at least 24 h after admission in patients with diabetes was associated with significantly higher odds of developing surgical-site infections (adjusted odds ratio 4·11, 95 per cent confidence interval 1·11 to 15·22; P = 0·034) and a longer hospital stay. For patients with no diabetes, however, delaying cholecystectomy had no impact on complications or length of hospital stay. Conclusion: Patients with diabetes who undergo laparoscopic cholecystectomy 24 h or more after admission may have an increased risk of postoperative surgical-site infection and a longer hospital stay than those undergoing surgery within 24 h of admission. Abstract : Delay increases risk in diabetes